NATURAL LANGUAGE PROCESSING AND MACHINE LEARNING - Prakash Singh (International Journal of Multidisciplinary Research and Studies, 2021)
Language is a means of communication that enables us to read, write, and even converse verbally with one another. For instance, we think, make judgements, and form plans, as well as a variety of other things, in natural language; more specifically, in words. However, the most important problem that we face in this age of AI is determining whether or not it is possible for humans and computers to interact in a way that is comparable. In other words, is it possible for humans and computers to interact with one another using the human language? The development of natural language processing systems is a problem for us since computers need organized data, yet human speech is unstructured and often confusing in its nature. In this sense, we might say that Natural Language Processing (NLP) is the sub-field of Computer Science, in particular Artificial Intelligence (AI), that is concerned with allowing computers to interpret and process human language. AI is the more general term for this area of research. Programming computers to be capable of analyzing and processing vast amounts of natural language data is the primary objective of NLP from a purely technical stand point.